Characterization Of Rambutan (Nephelium lappaceum L.) Seed Fat And Its Mixture With Cocoa Butter For Potential Application In Dark Chocolate - Hassan, Luma Khairy (2018)
Rambutan seed is one of rambutan by-product that has a potential to be utilized, especially as rambutan seed fat (RSF) and these fats can be partially incorporated into cocoa butter (CB). In this study, the fat from six days fermented and roasted rambutan seed was mixed with different proportions of cocoa butter, namely, 100/0, 80/20, 60/40, 40/60, 20/80, and 0/100 (w/w) CB to RSF, as CB, M1, M2, M3, M4 and RSF respectively. The changes that occurred to the physical properties and thermal stability were investigated. The results suggested that certain mixtures of CB and RSF, such as M1 (80%CB+20%RSF) exhibited the peak maxirnum during thermal behavior, polymorphism, morphology, and solid fat content of M1 sample similar to that of CB.